1978
DOI: 10.1002/prac.19783200405
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Derivatives and Related Compounds. VIII [1]. Routes for the Synthesis of 3,5‐Diaminopyrazoles, 2‐Aminopyrazolo[1,5‐a]pyrimidines and 5‐Aminopyrazolo[1,5‐a]pyrimidines

Abstract: Pyrimidinderivate und verwandte Verbindungen. VIII. Neue Synthesemöglichkeiten für 3,5‐Diaminopyrazole, 2‐Aminopyrazolo[1,5‐a]‐pyrimidine und 5‐Aminopyrazolo‐[1,5‐a]‐pyrimidine Während die 3,5‐Diacylamidopyrazole 2a–c durch Umsetzung von 3,5‐Diamino‐4‐phenylazopyrazolen 3 mit Schwefelsäure und Fettsäuren erhalten werden, entstehen die 3,5‐Diaminopyrazole 1 beim Erhitzen der Pyrazole 3 mit Schwefelsäure. 2‐Amino‐6,7‐dihydro‐5‐methyl‐7‐oxopyrazolo [1,5‐a] pyrimidin (4) erhält man durch Entfernung der Phenylazogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…22 Thus, the attempted closure of a pyridine ring in com pounds 9a,b in acetic anhydride failed. This objective was achieved by using strong acid agents for activation of the indole C=O group.…”
Section: Methodsmentioning
confidence: 98%
“…22 Thus, the attempted closure of a pyridine ring in com pounds 9a,b in acetic anhydride failed. This objective was achieved by using strong acid agents for activation of the indole C=O group.…”
Section: Methodsmentioning
confidence: 98%
“…Noteworthy, some authors believed (no evidence has been provided) that the endocyclic NH group is the most nucleophilic center in these compounds, although the experimental results (Al-Shiekh et al, 2004;Al-Omran and El-Khair, 2006;Dawood et al, 2005;Ege and Gilbert, 1979a;Ege et al, 1984;Elagamey et al, 1986;Elnagdi et al, 1976;1981;El-Ghandour Ahmed Hafez et al, 1992;Joshi et al, 1983;Kočevar et al, 1976) showed that such compounds could be successfully diazotized at the cost of the exocyclic NH 2 group which is consistent with the fundamentals of chemistry (Scheme 1).…”
Section: Relative Nucleophilicity Of the Amino And Imino Groupsmentioning
confidence: 99%
“…That is involved in the endocyclic N-1 nitrogen (Scheme 18). Elnagdi et al (1978) reported that 3,5-diaminopyrazole (47) reacted with acrylonitrile in refluxing aqueous pyridine to afford the corresponding 3,5-diamino-1-β-cyanoethyl pyrazole (Scheme 19).…”
Section: Relative Nucleophilicity Of Nh 2 Groupmentioning
confidence: 99%
See 1 more Smart Citation